Prevalence of fungal infections in a patient cohort in The Gambia: Identification and characterization of three priority fungal species in patients with symptoms suggestive of TB - Zackary Salem-Bango; Mary Basiru Njai; Zainab Tambajang; Tessa Rose Cornell; Jayne Sutherland; Karen Forrest; Omai Garner; Behzad Nadjm; Saffiatou Darboe; Basil Sambou; Sheikh Jarju (PLoS ONE, 2026)
Invasive fungal infections are an increasing global health concern, particularly in low-resource settings where diagnostic capacity is limited. In The Gambia, where tuberculosis is highly prevalent, fungal infections may be misdiagnosed as mycobacterial disease due to overlapping clinical symptoms and limited access to fungal testing. This study aimed to determine the presence of three priority fungal pathogens by the World Health Organization (WHO) classification system— Aspergillus species ( spp .), Histoplasma spp. , and Pneumocystis jirovecii —in patients with symptoms suggestive of tuberculosis, and to develop a molecular tool to support future surveillance. A multiplex quantitative polymerase chain reaction assay was developed and validated for simultaneous detection of Aspergillus spp. , Histoplasma spp. , and Pneumocystis jirovecii DNA in human sputum. The assay was applied to 273 stored sputum samples collected from adult patients presenting with respiratory symptoms concerning for tuberculosis in The Gambia. The multiplex assay demonstrated high sensitivity and specificity, detecting as few as ten DNA copies per reaction for each target. Among the 273 sputum samples analyzed, Aspergillus DNA was identified in five samples (1.8%), Pneumocystis jirovecii DNA in three samples (1.1%), and no samples were positive for Histoplasma . Cough and weight loss were the most frequently reported symptoms among participants with positive results. This study represents the first molecular detection of Aspergillus spp. and Pneumocystis jirovecii in adults in The Gambia. These findings suggest that fungal colonization or infection may occur in a small proportion of patients presenting with tuberculosis-like symptoms. The multiplex molecular platform developed here provides an accessible approach for fungal surveillance and may improve diagnosis and management of fungal infections in resource-limited settings.